Shielding Public Health: Indonesian National Police (INP)’s Measure Against COVID-19 Vaccine Certificate Forgery - Bayuna, Kadek Ari; Adnya Suasti, Ni Made; Syahputra, Aulia Noprizal (Jurnal Ilmu Kepolisian, 2024)
The purpose of this study is to discuss the benefits of implementing several strategies carried out during the COVID-19 period. COVID-19 vaccine certificate forgery has posed a threat to public health. The Indonesian National Police (INP) has implemented various strategies to overcome this crime. The intervention strategies involve early detection and prevention, such as cyber patrol, border control, public involvement, and strict law enforcement. Other countries have also carried out similar measures; however, there are several additional strategies, such as the formation of a special force as well as utilizing blockchain technology for a more secure digital vaccine certificate system. These strategies could be a benchmark for the INP in handling cases of letter forgery.